Fatal Coronavirus Disease 2019-associated Pulmonary Aspergillosis; A Report of Two Cases and Review of the Literature - Shiema Abdalla (9538596) (2020)
Coronavirus Disease 2019 (COVID-19)-associated pulmonary aspergillosis is an emerging entity. We report two fatal cases of putative COVID-19-associated pulmonary aspergillosis. Both cases were diagnosed on the basis of respiratory tract cultures yielding Aspergillus species and otherwise unexplained clinical and radiological deterioration. Existing published literature on COVID-19-associated pulmonary aspergillosis indicate poor outcomes and high mortality. CAPA should be considered in patients with critical COVID-19 who have unexplained progressive respiratory failure despite optimized supportive care. Diagnostic work-up should be initiated as early as possible and should ideally include fungal cultures, galactomannan detection and Aspergillus PCR on tracheal aspirates or broncho-alveolar lavage fluid. Empiric systemic antifungal therapy may be justified in selected cases, pending diagnostic work up results. Large, multi-center studies are required to further understand the pathogenesis of invasive aspergillosis in COVID-19, and the optimal diagnostic and treatment strategies. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2020.e00935